The Implementation of Accounting Conservatism Principles - Devi Permatasari; Ahmad Rudi Yulianto (The Indonesian Journal of Accounting Research, 2020)
This research investigates the influence of Company Growth, Investment Opportunity Set (IOS), and Managerial Ownership toward the application of accounting conservatism principles at mining companies listed in Indonesia Stock Exchange (IDX). This research used secondary data from IDX in 2014-2016. The sample of this research used purposive sampling technique. Based on purposive sampling method, the number of the samples were 21 companies. The data analysis technique used multiple linier regression analysis. The results of this research show that company growth and managerial ownership has negative influence toward accounting conservatism principle, meanwhile investment opportunity set has positive influence toward the application of accounting conservatism principle.